Customer repurchase intention in service business: a case study of car repair service business - Prasetya, Yafet Eka; Sianturi, Julfree (Management and Entrepreneurship: Trends of Development, 2019)
The aim of this study is to determine the relationship between behavioural intention with customer repurchase intention, customer satisfaction, perceived service quality, perceived product quality and perceived price fairness in automobile industry, particularly in service garage. This study is specified at particular authorized automobile workshops in Indonesia. The non-probability purposive sampling was performed to obtain the samples of this research. Methodology: the survey was conducted online, using the main instrument of the data collection – the questionnaire which was adopted from previous researchers. The samples were obtained from a survey conducted for two weeks with 174 respondents. The four set of variables were then tested to ensure the validity and reliability along with the assumption test to ensure the normality, linearity, homoscedasticity and multi-collinearity, which was concluded as powerful enough to be used for this research. The statistical analyses results have supported all hypotheses stated in the research. As a result the study found positive and significant relationship of perceived service quality, perceived product quality, and perceived price fairness with customer satisfaction. In addition, in the second stage, customer satisfaction was also proven to have significant and positive relationship with repurchase intention. This study can be improved by adding the sample numbers, enlarge the samples with different car brands, and have further study on additional dependent variables. However, the current result has provided valuable inputs for automobile service garage to increase the customer repurchase intention.JEL Classification: M21, M31, M30.